PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI TOKO WN TELANG PADA MAHASISWA UNIVERSITAS TRUNOJOYO MADURA - Camelia; Triana Setiyarini (STKIP Subang, 2026)
This study analyzes the phenomenon occurring at Toko WN Telang, Madura, which shows a reliance of customers on competitive pricing in determining their satisfaction. However, the aspect of service quality appears to be overlooked, despite its importance in creating a satisfying shopping experience. This research aims to analyze the impact of price and service quality on customer satisfaction at Toko WN Telang. The method used is quantitative with a multiple linear regression approach, involving 60 respondents from Universitas Trunojoyo Madura. Data was analyzed using SmartPLS 4 software. The results indicate that price has a significant effect on customer satisfaction, while service quality does not have a significant impact. This study provides new contributions by recommending that store owners enhance friendliness and attentiveness in service to strengthen customer satisfaction and loyalty. These findings can serve as a reference for retail business strategies to enhance competitiveness in a competitive market.